Some may argue is more simplified, but it's a matter of personal preference.
Ok, so I have this expression, and I need some help on it:
15abc - ab + 3ab
I'm guessing that first you go: ab + 3ab (cos ab= 1ab, and 3ab and ab are therefore like terms)
That would then leave me with 15abc - 4ab
That is what I understand so far, but can this expression be simplified further?
If so, how ?
THANKS!
The method is correct, but you missed a minus sign:
15abc - ab + 3ab = 15abc + (-ab + 3ab) = 15abc + (2ab)
Now notice that each term has a common ab in them. Thus
15abc + 2ab = 15(ab)c + 2(ab) = 15c(ab) + 2(ab) = (15c + 2)ab
(15abc = 15(ab)c = 15c(ab) due to the commutative property of real numbers.)
-Dan